EFEKTIFITAS PUASA DALAM MENINGKATKAN DISIPLIN BERIBADAH BAGI MASYARAKAT DESA KARDULUK SUMENEP - Abdul Munib (Universitas Islam Madura, 2019)
Fasting is the fourth pillar of Islam, which is given to Muslims. The essence of fasting is the control of things that can cancel or reduce the value of fasting. So that, this worship can be a means to shape physical and spiritual health, as well as a medium of education towards quality human beings. Some Karduluk people see fasting as a mere obligation whose motivation is to get reward and avoid torture in the hereafter, there are also those who view it as a spiritual need for humans to always relate to their Lord, which is driven by a deep sense of love for God . Worship for the Karduluk community is interpreted as self-servitude, in which humans are positioned as servants of God who must submit and obey all His commands. Worship is not only in the sense of ritual worship, but also includes all human good deeds which are intended as worship. Fasting is still an effective means to increase discipline in worship, both ritual worship and social worship. This is because fasting which is carried out seriously will lead people to be disciplined, devoted to Allah Almighty. And it is this taqwa that provides a way for humans to always obey all the rules of God without the need for external supervision.